2016
DOI: 10.1162/rest_a_00519
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Likelihood Estimation and Inference for Approximate Factor Models of High Dimension

Abstract: An approximate factor model of high dimension has two key features. First, the idiosyncratic errors are correlated and heteroskedastic over both the cross- Monte Carlo simulations show the method is easy to implement and an application to the U.S. yield curves is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 30 publications
5
72
0
1
Order By: Relevance
“…Doz, Giannone, and Reichlin (2012) proved the consistency of the common factor estimators for their true underlying values, while Bai and Li (2016) have also obtained rates of convergence and asymptotic variances under some restrictions. Doz, Giannone, and Reichlin (2012) proved the consistency of the common factor estimators for their true underlying values, while Bai and Li (2016) have also obtained rates of convergence and asymptotic variances under some restrictions.…”
Section: Conclusion and Extensionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Doz, Giannone, and Reichlin (2012) proved the consistency of the common factor estimators for their true underlying values, while Bai and Li (2016) have also obtained rates of convergence and asymptotic variances under some restrictions. Doz, Giannone, and Reichlin (2012) proved the consistency of the common factor estimators for their true underlying values, while Bai and Li (2016) have also obtained rates of convergence and asymptotic variances under some restrictions.…”
Section: Conclusion and Extensionsmentioning
confidence: 94%
“…The extension of our methods to models in which N∕T is nonnegligible would also constitute a very valuable addition with potentially interesting empirical applications. Doz, Giannone, and Reichlin (2012) proved the consistency of the common factor estimators for their true underlying values, while Bai and Li (2016) have also obtained rates of convergence and asymptotic variances under some restrictions.…”
Section: Conclusion and Extensionsmentioning
confidence: 94%
“…They showed that estimation under independent Gaussian errors still lead to consistent estimators for the large approximate factor model, even when the true model has cross-sectional and time series correlation in the idiosyncratic errors. Bai & Li (2012b) studied related issues for dynamic factors and cross-sectionally and serially correlated errors estimated by the maximum likelihood method.…”
Section: The Maximum Likelihood Methodsmentioning
confidence: 99%
“…As we have shown that our algorithm has a nonincreasing property, we terminate the algorithm when the reduction of the value of objective function is less than 10 −6 . We take the consistent estimates of Σ e and Λ given by Bai and Li (2016) as the initial values in our iterative procedure.…”
Section: Empirical Studymentioning
confidence: 99%